Underground Irkutsk: the Legend from the Past and the Prospective Development - Druzhinina, Inna; Kholyavko, Anastasia (project baikal, 2019)
The article studies the evolution of underground urbanistics from a functional point of view. It touches upon the myths and legends about underground Irkutsk, as well as the underground space development as prospective development of its historical center with preservation of its architectural outlook.
Keywords: underground urbanistics; catacombs; development of the historical center